Strengthening the Local Government System to Improve Public Service Delivery, Accountability and Governance - Tumushabe, Godber; Ssemakula, Eugene Gerald; Mbabazi, Jonas (. ACODE, 2012)
The Uganda Local Government Councils Score Card is a tool that assesses the performance of elected leaders at the district level. Since its launching in 2009, three assessments have been conducted including the current one for the financial year 2011/2012. The current score card is unique in one particular respect. It covers the first year in office for the officials who were elected in 2011 for a five year term of office. The score card can therefore be used by the leaders to benchmark how they are delivering in their mandate to improve public service delivery, promote accountability and strengthen the foundation for good governance